Digital trust and institutional assurance in the sharing economy from consumer and intermediary view. (28th May 2020) - Liu, Xiaodan; Yuan, Chunhui; Hafeez, Muhammad
The sharing economy is a new peer-to-peer online business model, where an order is made online and fulfilled offline. It involves only the transfer of usage rights, not property rights. The above characteristics lead to higher uncertainty and new risks. It is essential to create and ensure a trusted transactional context to reduce the risk of participating in the sharing economy. This study focuses on the factors influencing consumer's trust in the platform. The model is examined with 267 valid consumer samples. The results show that the trustworthiness of the platform is strongly related to consumer's trust in the platform. The institutional assurance has a direct impact on the trustworthiness of the platform and has a direct and indirect impact on consumer's trust in the platform. There is a strong trust transfer from trust in the platform to trust in suppliers which further promotes consumer's participation intention.